Observation of diffuse scattering in scanning helium microscopy. Issue 43 (28th October 2022) - Lambrick, S. M.; Bergin, M.; Ward, D. J.; Barr, M.; Fahy, A.; Myles, T.; Radić, A.; Dastoor, P. C.; Ellis, J.; Jardine, A. P.
Abstract : By studying well defined geometries (microspheres) in scanning helium microscopy (SHeM) the default scattering distribution for technological surfaces in SHeM is found to be diffuse and approximately cosine. Abstract : In understanding the nature of contrast in the emerging field of neutral helium microscopy, it is important to identify if there is an atom–surface scattering distribution that can be expected to apply broadly across a range of sample surfaces. Here we present results acquired in a scanning helium microscope (SHeM) under typical operating conditions, from a range of surfaces in their native state, i.e. without any specialist sample preparation. We observe diffuse scattering, with an approximately cosine distribution centred about the surface normal. The 'cosine-like' distribution is markedly different from those distributions observed from the well-prepared, atomically pristine, surfaces typically studied in helium atom scattering experiments. Knowledge of the typical scattering distribution in SHeM experiments provides a starting basis for interpretation of topographic contrast in images, as well as a reference against which more exotic contrast mechanisms can be compared.